Hyaluronic acid-modified cationic niosomes for ocular gene delivery: improving transfection efficiency in retinal pigment epithelium. (21st June 2018) - Qin, Yanmei; Tian, Yongfeng; Liu, Yang; Li, Dong; Zhang, Hua; Yang, Yeqian; Qi, Jianping; Wang, Hao; Gan, Li
Abstract: Objectives: Recent years, gene therapy to treat retinal diseases has been paid much attention. The key to successful therapy is utilizing smart delivery system to achieve efficient gene delivery and transfection. In this study, hyaluronic acid (HA) modified cationic niosomes (HA-C-niosomes) have been designed in order to achieve retinal pigment epithelium (RPE) cells targeted gene delivery and efficient gene transfection. Methods: Cationic niosomes composed of tween 80/squalene/1, 2-dioleoyl-3-trimethylammonium-propane (DOTAP) were prepared by the ethanol injection method. After that, HA-DOPE was further added into cationic niosomes to form HA-C-niosomes. Cellular uptake and transfection have been investigated in ARPE-19 cells. In vivo pEGFP transfection efficiency was evaluated in rats. Key findings: Twenty percentage HA-C-niosomes were about 180 nm, with −30 mV, and showing spherical shape in TEM. 2 times higher transfection efficiency was found in the group of HA-C-niosomes with 20% HA modification. No toxicity was found in niosome preparations. In vivo evaluation in Sprague Dawley (SD) rats revealed that HA-C-niosomes could specifically target to the retina layer. In the group of pEGFP-loaded HA-C-niosomes, 6–6.5 times higher gene transfection has been achieved, compared with naked pEGFP. Conclusions: Hyaluronic acid-C-niosomes might provide a promising gene delivery system for successful retinal gene therapy.